Valid garnet-biotite thermometer: A comparative study (Journal of Nepal Geological Society, 2019)
The abundance of garnet-biotite pair in a wide range of rocks mainly from upper green schist to granulite facies has made it one of the most widely used pairs for estimation of temperature at which once rocks equilibrated. In last four decades, more than 20 thermometer models of garnet-biotite pair have been proposed. To find the suitability of models, twenty-one thermometers formulated by a number of scholars since 1976 is considered. 27 sample data of granulites from the global literature were collected and processed through the “Gt-Bio.EXE” software. We conclude that four models are the most valid and reliable of these kinds of thermometers: Perchuk and Lavrente’va (1983); Thompson (1976); Ferry and Spear (1978) and Holdaway and Lee (1977).